The impact of CYP3A4 and CYP3A5 polymorphisms on anastrozole's pharmacokinetics and pharmacodynamics in post-menopausal breast cancer patients - Abubakar, Murtala Bello (2017)
Breast cancer is the second most frequent cancer among all cancer types and is by far the commonest cancer in women. Anastrozole is one of the first line drugs of choice in the treatment of breast cancer and is believed to be superior to tamoxifen. However, a significant proportion of patients treated with anastrozole experienced recurrences of breast cancer or developed severe adverse drug reactions. This interpatient variability is attributed to a number of factors such as genetic variations. Anastrozole is predominantly metabolized by CYP3A4 and CYP3A5 enzymes. The objective of this study was to determine the impact of CYP3A4 and CYP3A5 genetic polymorphisms on anastrozole’s pharmacokinetics and pharmacodynamics in postmenopausal breast cancer women. A total of 94 postmenopausal breast cancer women were recruited for this study. Patients’ socio-demographic data and clinical variables were recorded and blood samples were collected for DNA acquisition, hormonal and anastrozole serum levels. Genotyping of CYP3A4*18A and CYP3A5*3 was performed using the conventional polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP), while that of CYP3A4*4, CYP3A4*18B and CYP3A4*22 was carried out by a novel multiplex PCR-RFLP method. Serum anastrozole concentration was determined by an ultra-high performance liquid chromatography (UHPLC) method using a simple solid-phase extraction procedure. Our study reported that CYP3A4*18B G>A has a high frequency (0.48) among Malaysians and that CYP3A4*18A T>C and CYP3A5*3A>G occur in low (0.03) and high (0.64) frequencies respectively among Malaysians. No variant alleles of CYP3A4*4 and CYP3A4*22 were detected among all the subjects. Patients homozygous for CYP3A4*18B G>A and CYP3A5*3 A>G had lower and higher anastrozole serum levels respectively compared to those having the respective wild types or heterozygous variants. The multiplex PCR-RFLP method for the simultaneous detection of CYP3A4*4 A>G, CYP3A4*18B G>A and CYP3A4*22 C>T, was applied in genotyping of all the subjects. The newly developed UHPLC method demonstrated a good linearity over concentration ranges of 20 – 1600 ng/mL. The mean recovery for anastrozole was 88.17% with a limit of quantitation of 20 ng/ml. Variables such as patients’ age and time since commencement of anastrozole therapy were associated with higher risk of developing vasomotor symptoms and mood disturbances and/or vaginal dryness/dyspareunia respectively. No significant association was established between CYP3A4 and CYP3A5 genetic polymorphisms and anastrozole’s pharmacodynamics. The detected CYP3A4*18B G>A and CYP3A5*3 A>G alleles may serve as an important biomarkers of altered anastrozole metabolism in breast cancer patients receiving anastrozole in future.